2010
DOI: 10.1021/bi100372h
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Apo and Metal-Bound Forms of the UreE Protein from Helicobacter pylori: Role of Multiple Metal Binding Sites,

Abstract: Received March 10, 2010; Revised Manuscript Received July 15, 2010 ABSTRACT: The crystal structure of the urease maturation protein UreE from Helicobacter pylori has been determined in its apo form at 2.1 Å resolution, bound to Cu 2þ at 2.7 Å resolution, and bound to Ni 2þ at 3.1 Å resolution. Apo UreE forms dimers, while the metal-bound enzymes are arranged as tetramers that consist of a dimer of dimers associated around the metal ion through coordination by His102 residues from each subunit of the tetrame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 32 publications
2
48
0
Order By: Relevance
“…4E). Previous studies have shown that Hp UreE is usually found as a dimer in solution [8, 9]; in addition crystal structures of metal-bound forms of HpUreE revealed that dimers of UreE dimers (“kissing” dimers) can associate around the metal ion (Cu 2+ , Ni 2+ or Zn 2+ ) through coordination by His102 residue [10]. Similar tetrameric forms have been reported in the case of Zn 2+ - bound UreE from Bacillus pasteurii [33,34] or Cu 2+ , Ni 2+ , or Zn 2+ - bound UreE from K. aerogenes [35].…”
Section: Discussionmentioning
confidence: 99%
“…4E). Previous studies have shown that Hp UreE is usually found as a dimer in solution [8, 9]; in addition crystal structures of metal-bound forms of HpUreE revealed that dimers of UreE dimers (“kissing” dimers) can associate around the metal ion (Cu 2+ , Ni 2+ or Zn 2+ ) through coordination by His102 residue [10]. Similar tetrameric forms have been reported in the case of Zn 2+ - bound UreE from Bacillus pasteurii [33,34] or Cu 2+ , Ni 2+ , or Zn 2+ - bound UreE from K. aerogenes [35].…”
Section: Discussionmentioning
confidence: 99%
“…These additional proteins have regions rich in various combinations of metal-binding amino acids and can bind multiple nickel ions, which may compensate for the lack of a His-rich region in either HpHypB or the H. pylori UreE protein (30). Furthermore, the reduced nickel-binding capacity of H. pylori UreE has been suggested to be a plausible reason for the supplemental involvement of HpHypB in urease bioassembly (60). In support of this hypothesis, H. pylori UreE with a synthetically attached His-rich sequence can rescue the urease activity in H. pylori hypA and hypB deletion mutants (3).…”
Section: Discussionmentioning
confidence: 99%
“…The full-length zinc-bound S. pasteurii UreE dimeric structure (code 1EAR) exhibits close similarity to the K. aerogenes protein, lacks the C-terminal His-rich region and the two peripheral sites, and binds a single Zn 2ϩ ion (presumably substituting for Ni 2ϩ ) at the interfacial site (63). Structures of several forms of H. pylori UreE are known, including the nickel-bound species (codes 3L9Z and 3TJ8) (64,65), in which the Ni 2ϩ is coordinated at the interfacial site with an additional His residue provided from the C terminus. These highly soluble proteins are proposed to bind metal ions in the cytoplasm and specifically deliver nickel to urease within the complex of other accessory proteins.…”
Section: Ured/ureh: Scaffold For Recruitment Of Other Accessory Protementioning
confidence: 99%